The Role of Performance Appraisal in Driving Economic Efficiency: Mediating Effects of Work Motivation and Job Satisfaction - Fadlilah, Muhammad Arif; Martini, Ida Ayu Oka (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study explores how performance appraisal affects work motivation, job satisfaction, and performance, utilizing SEM-PLS. The research employed primary data acquired through a questionnaire. Government Valuers at the Directorate General of State Assets Management across Indonesia constitute the research population. The analysis findings conclude that work motivation and job satisfaction mediate the relationship between the performance appraisal system and performance. Furthermore, job satisfaction is a strong predictor of employee performance, making this an exciting consideration for interpretation. Performance appraisal itself does not show a direct relationship with performance. These findings indicate that motivation and job satisfaction are essential factors in performance appraisal that influence the performance of Government Valuers. Developing objective and accurate performance appraisals will improve employee performance while considering work motivation and job satisfaction.